DESIGNING EDUCARDS AS VISUAL AIDS OF PROCEDURE TEXTS FOR STUDENTS WITH AUTISTIC SPECTRUM DISORDER - Meydianda, Dintania; Salam, Urai; Rezeki, Yanti Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is aimed to design EDUcards; the visual recipes of West Kalimantan Traditional Cuisine, as learning medium of procedure texts teaching in the classroom of year-9 autistic students. This developmental study was conducted to bridge the gap between desired and actual performance of procedure texts teaching and learning caused by the limited availability of supporting media in the West Kalimantan Autism School. There were three phases of ADDIE procedure implemented during the process of creating EDUcards namely Analyzing, Designing and Developing phase. To decide the perceived quality of EDUcards, an assessment rubric consisted of twelve traits was being provided. It was used by the expert to validate the acceptability of EDUcards as visual aids in the procedure texts teaching learning. The result of assessment rubric indicated that EDUcards have met both teacher and students expectation, and are reliable to support the teaching learning process of procedure texts for ninth grade autistic students. Keywords: EDUcards, visual aids, visual recipes, procedure texts, autisticstudents.